Die Umsetzung schulischer Inklusion nach der UN-Behindertenrechtskonvention in den deutschen Bundesländern - Steinmetz, Sebastian (Recht und Gesellschaft - Law and Society, 2021)
The study examines the current state of implementation of the UN Convention on the Rights of People with Disabilites (CRPD) with regard to the inclusion of children with special needs in mainstream schools in the German states. It provides a comprehensive structural analysis of this area. Article 24 of the convention obliges the signatory states to guarantee an inclusive education system at all levels. In order to examine the extent to which the German states (Länder) implement this requirement in law and practice in their school systems, empirically measurable indicators were formed on the basis of the provisions of the CRPD. Even more than 10 years after ratification of the CRPD, the majority of the German states still face major challenges. Only a few German states are currently undergoing a process of transformation, which is why the majority of children and young people with special educational needs continue to be trained in special and segregated structures.